Overexpression of the Transcription Factor Azf1 Reveals Novel Regulatory Functions and Impacts β-Glucosidase Production in Trichoderma reesei - David Batista Maués; Jhonatan Christian Maraschin; Diego Ângelo Duarte; Amanda Cristina Campos Antoniêto; Roberto N. Silva (Journal of Fungi, 2023)
The fungus Trichoderma reesei is an essential producer of enzymes that degrade lignocellulosic biomass to produce value-added bioproducts. The cellulolytic system of T. reesei is controlled by several transcription factors (TFs) that efficiently regulate the production of these enzymes. Recently, a new TF named Azf1 was identified as a positive regulator of cellulase expression. Here, we investigated novel regulatory functions of Azf1 by its overexpression. In the mutant strain OEazf1, overexpression of azf1 was achieved under both repression and induction conditions. Although azf1 was more abundant in transcript and protein, overexpression of this TF did not activate transcription of the cellulase gene in the presence of the repressor glucose, suggesting that Azf1 may be subject to posttranslational regulation. In cellulose, the expression of swo, encoding the accessory protein swollenin, and the β-glucosidases cel1a, cel1b, cel3b, and cel3g increases in the early stages of cultivation. The increased production of these β-glucosidases increases the hydrolysis rate of cellobiose and sophorose, which activates carbon catabolite repression (CCR) and causes repression of cellulase genes and the regulator Xyr1 in the later stages of cultivation. Moreover, overexpression of azf1 led to increased cellulase activity in T. reesei during long-term cultivation in cellulose and sugarcane bagasse. Our results provide new insights into the mechanisms regulating Azf1 and novel genes that are important targets of this TF. This work contributes to a better understanding of the complex mechanisms regulating cellulase expression in T. reesei. It will contribute to the development of strains with higher production of these essential enzymes.